Establishing an Academic–Community Partnership to Explore the Potential of Barbers and Barbershops in the Southern United States to Address Racial Disparities in HIV Care Outcomes for Black Men Living With HIV. Issue 1 (February 2023) - Nwakoby, Chidiogo; Pierce, Leslie J.; Crawford, Robert; Conserve, Donaldson; Perkins, Jessica; Hurt, Sharon; Ahonkhai, Aima A.
Black men comprise most new HIV infections in the Southern United States and have worse HIV outcomes than their non-Black counterparts. We developed an academic–community partnership in Nashville, Tennessee, to explore opportunities to improve HIV outcomes for Black men. We recruited barbers to an HIV training and focus group discussion about prevention and potential barber/barbershop-based strategies to address HIV-related needs for Black men. We assessed HIV knowledge and stigma with validated scales and conducted thematic analysis on discussion transcripts. HIV-related stigma was low (1.8 of 15 points [ SD = 1.69]) among 13 participants of unknown HIV status (12 men and one woman). HIV knowledge increased among eight (67%) participants after receiving a brief HIV didactic. Participants described general health care barriers (e.g., the social norm that Black men do not go to the doctor until they are "damn near dead"), fears about unwanted HIV disclosure when seeking HIV testing or care, and community fears about negative stereotypes associated with HIV. Participants expressed enthusiasm about receiving more HIV-related training and utilizing communication skills and client/community relationships to serve as health educators and navigators. Barbers highlighted opportunities to disseminate HIV information in barbershops and combine HIV interventions with other health issues, such as COVID-19, and suggested that these interventions may help reduce HIV-related stigma. Our findings suggest that barbers and barbershops are an underutilized resource for disseminating HIV-related health information and engaging Black men in HIV and other important prevention and care activities such as COVID-19.